(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The potential human health issues resulting from the continuous consumption of drinking water containing low concentration levels of persistent emerging pollutants has raised some concerns. The presence of emerging pollutants in surface water bodies and ground-water in Canada together with absence of proper drinking water treatment processes in remote places has created the need for an effective and simple process for removal of emerging pollutants from drinking water. Low seasonal temperatures in regions such as Saskatchewan demand a removal process that is effective at temperatures lower than room temperature. Adsorption with granular activated carbon is a well-established and effective method for removal of organic compounds from drinking water. There are a large number of reports on removal of organic compounds by activated carbon in literature however, the effectiveness of adsorption of emerging pollutants with granular activated carbon is not clear. Effectiveness of ozone treatment for oxidation of emerging pollutants is reported in literature however, effectiveness of regeneration of adsorbents saturated with emerging pollutants with ozone has not been investigated extensively.The rapidly increasing population, depleting water resources, and climate change resulting in prolonged droughts and floods have rendered drinking water a competitive resource in many parts of the world. The development of cost-effective and stable materials and methods for providing the fresh water in adequate amounts is the need of the water industry. Traditional waterwastewater treatment technologies remain ineffective for providing adequate safe water due to increasing demand of water coupled with stringent health guidelines and emerging contaminants. Nanotechnology-based multifunctional and highly efficient processes are providing affordable solutions to waterwastewater treatments that do not rely on large infrastructures or centralized systems. The aim of the present study is to review the possible applications of the nanoparticlesfibers for the removal of pollutants from waterwastewater.